Dietary acculturation among black immigrant families living in Ottawa—a qualitative study. Issue 3 (4th May 2018) - Blanchet, Rosanne; Nana, Constance P.; Sanou, Dia; Batal, Malek; Giroux, Isabelle
ABSTRACT: The study explores the dietary acculturation process among first-generation immigrant families from sub-Saharan Africa or the Caribbean living in Ottawa (Canada). In-depth qualitative interviews were conducted with 12 mothers. The interaction between accelerating factors and other mediating factors resulted in a spiral of dietary changes triggered by immigration. The spiral evolved at different paces from traditional to acculturated and toward healthy or unhealthy diets and was hard to stop or to change in its direction once it started. Findings call for enhancing immigrant mothers' food access, food literacy and nutrition-related parenting skills, and their children's school food environment.